Synthesis of Amino Acid Schiff Base Nickel (II) Complexes as Potential Anticancer Drugs In Vitro - Yang Li; Jianfang Dong; Peiran Zhao; Ping Hu; Dawei Yang; Lei Gao; Lianzhi Li (Bioinorganic Chemistry and Applications)
Three hexacoordinated octahedral nickel (II) complexes, [Ni (Trp-sal) (phen) (CH3OH)] (1), [Ni (Trp-o-van) (phen) (CH3OH)]•2CH3OH (2), and [Ni (Trp-naph) (phen) (CH3OH)] (3) (where Trp-sal = Schiff base derived from tryptophan and salicylaldehyde, Trp-o-van = Schiff base derived from tryptophan and o-vanillin, Trp-naph = Schiff base derived from tryptophan and 2-hydroxy-1-naphthaldehyde, phen = 1, 10-phenanthroline), have been synthesized and characterized as potential anticancer agents. Details of structural study of these complexes using single-crystal X-ray crystallography showed that distorted octahedral environment around nickel (II) ion has been satisfied by three nitrogen atoms and three oxygen atoms. All these complexes displayed moderate cytotoxicity toward esophageal cancer cell line Eca-109 with the IC50 values of 23.95 ± 2.54 μM for 1, 18.14 ± 2.39 μM for 2, and 21.89 ± 3.19 μM for 3. Antitumor mechanism studies showed that complex 2 can increase the autophagy, reactive oxygen species (ROS) levels, and decrease the mitochondrial membrane potential remarkably in a dose-dependent manner in the Eca-109 cells. Complex 2 can cause cell cycle arrest in the G2/M phase. Additionally, complex 2 can regulate the Bcl-2 family and autophagy-related proteins.